Clinical Sports Medicine - Wilhelm A; 4; Herbsleb M; Dittmar C; Rüdrich P; Schürer A; Wüstenfeld J; 5; Kastner T; 5; Wolfarth B; 4; et al. (Deutsche Zeitschrift für Sportmedizin, 2021)
Purpose: The aim of the present investigation was to compare the blood lactate concentration (BLC) vs. heart rate (HR) relationship of incremental treadmill (ITR) vs. prolonged field running (PFR) in order to provide a mathematical equation allowing to adjust HR-based intensity zones, derived from non-steady state ITR-exercise, to ensure their transposition to -and application for prolonged field running.Methods: Sixteen junior elite cross-country (XC) skiers were examined in ITR and PFR, where subjects were instructed to complete four consecutive self-paced 2.500 m-runs in undulating terrain at different exercise intensities. BLC obtained from both settings were compared at given HR, obtained from each of the four loops during PFR.Results: A two-way 4 x 2 repeated measures analysis of variance (ANOVA) showed a statistically significant main effect of stage (p< .001) and test protocol (p< .001), as well as a significant interaction effect between these two factors (p<.001). Post-hoc calculated paired-samples t-test showed significantly lower BLC from ITR compared to that obtained from PFR at any loop/HR level. Cohens d revealed large effect sizes (loop 1: -; loop 2: 1.110.23 vs. 1.640.38 mmol l-1, p<.001, d=1.71; loop 3: 1.790.38 vs. 4.211.19, p<.001, d=2.12; loop 4: 3.080.75 vs. 9.161.67, p<.001, d=3.99). Conclusion: For BLC-levels ranging from 1.5-6 mmol l-1, coaches should subtract approx. 15 beats min-1 from the HR obtained during a lab test identical to that used in the present study in order to exercise at comparable BLC during prolonged training in the field.Key Words: Heart Rate, Training Zones, T-Test, Two-Way Measures Analysis of Variance (ANOVA)